Dominasi Ekonomi Jepang Terhadap Indonesia dalam Perdagangan Elektronik Indonesia - Ucu Juan Nurhidayat (Universitas 17 Agustus 1945 Jakarta, 2018)
Abstract Ties of cooperation between Indonesia and Japan have established more than half a century . Along the way , Japan has played a role in encouraging the economic development of Indonesia . The author discusses the economic dominance of Japan against Indonesia in Electronics Sector .As we know that the Japanese economic dominance in the electronics sector Indonesia was caused by the absorption of Indonesian electronics market is so big on electronics from Japan , the Indonesian government issued a regulation of import substitution policies , enactment of liberal economic policies through agreements such as the WTO , in addition to the confidence ndonesia society against the Japanese electronics so great because they are relatively affordable and good quality . Making Japanese electronics goods spread in Indonesia so it causes in cooperation between Indonesia and Japan carried more favorable to the Japanese rather than Indonesian .In looking at this issue of national importance is the basis for cooperation between Indonesia and Japan , because basically between Indonesia and Japan 's economic cooperation with a view to the welfare of society , although in fact the same work in the country of Japan is more profitable than the country of Indonesia .This is possible because, according to David Ricardo in the theory that free trade , technological mastery and hard work into success factors of a country . For a country that controls the technology will increasingly benefit from free trade , while only relying on the country 's natural wealth will be lost in international competition .With that condition more clearly that Japan is more advantaged than Indonesia Key Words: Domination, electronic Trade, National Interes Abstrak Hubugan kerjasama antara Indonesia dan Jepang telah terjalin lebih dari setengah abad. Selama itu pula, Jepang telah turut berperan dalam mendorong pembangunan ekonomi Indonesia. Penulis membahas mengenai Dominasi Ekonomi Jepang terhadap Indonesia Dalam Sektor Elektronik.Seperti kita ketahui bahwa dominasi ekonomi Jepang dalam sektor elektronik Indonesia itu disebabkan oleh daya serap pasar elektronik indonesia begitu besar terhadap elektronik dari jepang, regulasi pemerintah Indonesia yang mengeluarkan kebijakan substitusi impor , diberlakukannya kebijakan-kebijakan ekonomi liberal melalui kesepakatan seperti WTO, di samping itu kepercayaan masyarakat ndonesia terhadap elektronik Jepang begitu besar karena harganya relatif terjangkau dan kualitasnya bagus. Sehingga menjadikan barang- barang elektronik Jepang begitu menyebar di Indonesia hal itu menyebabkan kerja sama yang di laksanakan antara Indonesia dengan Jepang lebih menguntungkan kepada pihak Jepang daripada Indonesia.Dalam melihat masalah ini kepentingan nasional menjadi dasar bagi hubungan kerja sama antara Indonesia Jepang, karena pada dasarnya antara Indonesia dan Jepang melakukan kerja sama ekonomi itu dengan tujuan untuk mensejahterakan masyarakatnya, walaupun pada kenyataanya dalam kerja sama ini negara Jepang lebih di untungkan daripada negara Indonesia.Hal itu dimungkinkan karena menurut David Ricardo dalam teori perdagangan bebas bahwa, penguasaan teknologi dan kerja keras menjadi faktor keberhasilan suatu negara. Bagi suatu negara yang menguasai teknologi akan semakin diuntungkan dengan adanya perdagangan bebas ini, sedangkan negara yang hanya mengandalkan kepada kekayaan alam akan kalah dalam persaingan internasional.Dengan kondisi itu lebih jelas bahwa Jepang lebih diuntungkan ketimbang Indonesia. Kata Kunci: Dominasi, Perdagangan Elektronik, Kepentingan Nasional